Mapping land and water supported livelihoods, stakeholders, policies and governance mechanism in the Lower Kafue Basin, Southern Zambia - Ng’onga, M.; Mapedza, Everisto D.; Siamudaala, V.; Muzungaire, L. (International Water Management Institute (IWMI). CGIAR Initiative on Aquatic Foods, 2024)
Aquatic foods are important and hold a significant role in the global food system through income, food and employment. The Lower Kafue Basin is one of the most important ecosystems in Zambia in providing fisheries, livestock, wildlife, forestry, irrigation farming, hydro-electricity, water for industrial and municipal use services. These multiple and competing uses of the Kafue River and its basin are some of the drivers that are exerting pressure on the ecosystem and challenging its capacity to continue to provide livelihood services to the people in the basin. Hence, investing in effective aquatic food landscape governance through the development of a Multi-Stakeholder Platform and Stakeholder Engagement Strategy for Aquatic Food Systems is expected to contribute towards sustainable and integrated development. A literature review was conducted on the Aquatic Food Systems for the landscape and multi-stakeholder platform/engagement in Zambia. Key informant interviews and Focus Group Discussions (FGDs) were conducted with Government officials, Non-governmental Organizations, Traditional Authorities and Resource Users to have an in-depth understanding. Findings indicated that agriculture is one of the dominant sectors with about 0.1 to 20 hectares per farmer under cultivation contributing 17% of the national maize production. The Lower Kafue Basin has the largest population of livestock within the country with a cattle population estimated at 92,900 heads; Namwala district alone accounts for 24.2% of the country’s total livestock population. Fish production in the Lower Kafue Basin represents approximately 7% of the total fisheries industry in Zambia. Wildlife distribution is largely attributed to the diversity and complexity of habitats while forestry resources in Southern Province of Zambia are estimated at 4,673,000 hectares of standing forest area. Based on this review, it was recommended to design and develop the Multistakeholder Platform (MSP) and Stakeholder Engagement Strategy (SES) that should respond to the Multi-Sectoral challenges in the management of the Lower Kafue Basin. The report also recommends that a cost-benefit sharing and financing mechanism should be devised to sustain conservation and management of the Lower Kafue Basin.